Clinical characteristics, treatments, outcome, and prognostic factors of severe autoimmune encephalitis in the intensive care unit: Standard treatment and the value of additional plasma cell–depleting escalation therapies for treatment‐refractory patients. (17th October 2022) - Schwarz, Lisa; Akbari, Nilufar; Prüss, Harald; Meisel, Andreas; Scheibe, Franziska
Abstract: Background and purpose: To investigate severe autoimmune encephalitis (AE) in the intensive care unit (ICU) with regard to standard treatment in responsive patients and additional escalation therapies for treatment‐refractory cases. Methods: This retrospective, single‐center study analyzed medical records of ICU‐dependent AE patients for clinical characteristics, treatments, prognostic factors, and neurological outcome as quantified by modified Rankin Scale (mRS) and Clinical Assessment Scale for Autoimmune Encephalitis (CASE). Results: From 40 enrolled patients (median age = 52 years; range = 16–89 years) with AE mediated by neuronal surface antibodies (nsAb; 90%) and AE with onconeuronal antibodies (10%), 98% received first‐line therapy. Of those, 62% obtained additional second‐line therapy, and 33% received escalation therapy with bortezomib and/or daratumumab. Good neurological outcome, defined as mRS = 0–2, was observed in 47% of AE with nsAb (CASE = 5), 77% of anti‐N‐methyl D‐aspartate receptor encephalitis patients (CASE = 1), whereas AE patients with onconeuronal antibodies had the poorest outcome (mRS = 6, 100%). Treatment‐refractory AE patients with nsAb requiring escalation therapy achieved similarly good recovery (mRS = 0–2, 39%, CASE = 3) as patients improving without (mRS = 0–2, 54%, CASE = 4), although they presented a higher disease severity at disease maximum (mRS = 5 100% versus 68%, CASE = 24 versus 17; p = 0.0036), had longer ICU stays (97 versus 23 days; p = 0.0002), and a higher survival propability during follow‐up ( p = 0.0203). Prognostic factors for good recovery were younger age ( p = 0.025) and lack of preexisting comorbidities ( p = 0.011). Conclusions: Our findings suggest that treatment‐refractory AE patients with nsAb in the ICU can reach similarly good outcomes after plasma cell–depleting escalation therapy as patients already responding to standard first‐ and/or second‐line therapies. Abstract : Our retrospective study analyzed 40 patients with intensive care unit (ICU)‐dependent autoimmune encephalitis (AE) for clinical characteristics, diagnostics, prognostic factors, and clinical outcomes regarding standard treatment in responsive patients versus additional escalation therapies for treatment‐refractory cases. Our findings suggest that treatment‐refractory AE patients with neuronal surface antibodies (nsAb) in the ICU can reach similarly good outcomes after plasma cell–depleting escalation therapy as patients already responding to standard first‐ and/or second‐line therapies.